Needs Analysis for Developing a Digital Evaluation System for Micro-skills Achievement in the Merdeka Belajar-Kampus Merdeka (MBKM) Program - Henny Setiani; Yayat Ruhiat; Aan Hendrayana (Jurnal Pendidikan Indonesia Gemilang, 2025)
This study analyzed the requirements for a digital system to evaluate microskill achievement within the MBKM program at universities. A descriptive research method was employed, utilizing a Likert-scale-based questionnaire completed by 132 respondents, consisting of 66 students and 66 lecturers from six universities. The sample size was determined through Power Analysis with an effect size parameter (f) of 0,4. The findings reveal that the conventional evaluation system faces challenges, including unclear assessment standards, difficulties in converting microskills to credit point, and time-consuming processes. Both students and lecturers express the need for a digital system that is more transparent, efficient, and capable of enabling real-time monitoring and feedback. These findings form the basis for designing a more effective microskill evaluation system.